Recent advances in the application of ultrasound to meat and meat products: Physicochemical and sensory aspects - Barretto, Tiago Luis [UNESP]; Sanches, Marcio Augusto Ribeiro [UNESP]; Pateiro, Mirian; Lorenzo, Jose Manuel; Telis-Romero, Javier [UNESP]; da Silva Barretto, Andrea Carla [UNESP] (Taylor & Francis, 2022)
Ultrasound is an acoustic mechanical wave that, at intensities above 20 kHz, can cause cavitation, a phenomenon responsible for accelerating chemical reactions and/or causing changes in the microstructure of food. This technology has been studied in meat salting, as well as in products such as bacon, sausage, cooked ham, salami and bologna. The water holding capacity, color and instrumental texture and sensory acceptance of these products can be improved with the introduction of this technology. Thus, the objective of this review is to present an overview of the effects of ultrasound on the physicochemical and sensory properties of meat and meat products.
Keywords: Cavitation; instrumental texture; sensory acceptance; water holding capacity